A contribuição da contação de histórias para o processo de ensino-aprendizagem na educação infantil - Araújo, Rosãngela da Silva (Universidade Federal do Tocantins, 2023)
The present research has as a general objective to understand the importance of imagery texts in early childhood education for the formation of future readers. Its theme is the contribution of storytelling to the teaching-learning process in early childhood education. Bibliographic and qualitative research methodology was used. The contemporary Brazilian scenario shows the existence of many difficulties in education, especially when analyzing the low student performance in relation to reading and writing. In seeking to understand the genesis of the problem, studies focus on the various aspects of teaching and learning reading practices, highlighting the importance of developing pleasurable practices that involve the act of reading, assigning great importance to this stimulus in the students' training process readers. In general, what is recognized is that reading activities in the classroom are often discouraging, and that, depending on the way they are worked, end up generating a lack of stimulation and interest in relation to it. This bad relationship in relation to reading starts from the early grades and persists throughout school life and even beyond. In order to obtain satisfactory answers to this study, we outlined as a general objective, to understand the importance of imagery texts in early childhood education for the training of future readers. Among the main authors used in this research, we mention Abramovich (1991/2001/1995), Ferronatto (2006), Oliveira (2005), Souza and Bernardino (2011), Villardi (1997), among others, which enabled us to better understand about the topic. After the bibliographic survey, a field observation was made at the Municipal School of Full Time in the city of Miranorte - TO in pre-school classes. Stories represent effective indicators for challenging situations, as well as strengthening social, educational and affective bonds. Therefore, it is necessary for teachers to use this tool for the child's development, awakening small readers and stimulating the world of imagination.